Nova revija v primežu Službe državne varnosti - Šela, Ana (Annales. Series historia et sociologia, 2017)
Nova revija, the monthly magazine devoted to culture which was founded in 1982 with the signature of sixty Slovenian cultural workers and intellectuals, was one of the key elements that helped Slovenia achieve independence. Because of the critical views of the then political system and the topics that covered the secret history, the right to freedom of speech, national issues, the encroachment of human rights etc., the authors of the monthly were constantly monitored by the State Security Service (Slovenian SDV), and were often also subject to criminal proceedings against them. The SDV agents carefully monitored the authors and articles of Nova revija and prepared on a monthly, semi-annual, and annual basis general and also in-depth reports on the topics, ideas and controversies addressed by the authors in specifi c issues and likely in those to come. Also, they carefully monitored the editorial policy of the monthly and the opinion of the public and other cultural magazines regarding the articles in Nova revija. The cultural magazines had dealt with repressive institutions already in the 1950s, when attempts to set up magazines with taboo themes were quickly suppressed. Nova revija broke the stretch of cultural inactivity and resisted pressures and attempts for its abolishment. The 57th issue of the monthly, titled The Contributions for the Slovenian National Program, played a key role in the democratization of the Slovenian territory.
Keywords: censorship; cenzura; intelektualna opozicija; Intellectual opposition; Nova revija (periodicals); Nova revija (periodika); Služba državne varnosti; State Security Service